Genetic and antigenic analysis of Chlamydia pecorum strains isolated from calves with diarrhea - OHTANI, Akifumi; KUBO, Masahito; SHIMODA, Hiroshi; OHYA, Kenji; IRIBE, Tadashi; OHISHI, Daiki; ENDOH, Daiji; OMATSU, Tsutomu; MIZUTANI, Tetsuya; FUKUSHI, Hideto; MAEDA, Ken (Journal of Veterinary Medical Science, 2015)
Chlamydia pecorum (designated 22–58) was isolated in 2010 in HmLu-1 cells from the jejunum of a calf which died of necrotizing enterocolitis in Yamaguchi Prefecture, Japan. Immunohistochemical staining identified C. pecorum positive reactions in the jejunal villi. C. pecorum, designated 24–100, was isolated from the feces of a calf with diarrhea in another farm in Yamaguchi Prefecture in 2012. A significant increase in neutralizing antibody titers against C. pecorum was confirmed in paired sera. Nucleotide sequence identities of omp1 genes of the 2 isolates were 100%. The isolates were genetically and antigenically more closely related to C. pecorum Bo/Yokohama strain isolated from cattle with enteritis in Japan than to the other prototype strains, Bo/Maeda isolated from cattle with pneumonia and Ov/IPA isolated from sheep with polyarthritis. These results indicate that C. pecorum strains similar to 22–58 and 24–100 might be endemic in Yamaguchi Prefecture and cause enteric disease in cattle.